Time and Cost Optimization Analysis of Reservoir Building Work in Wosusokas Regional SPAM Project using Time Cost Trade Off Method - Maharani, Devita Putri; Setyawan, Ary; Setiono, Setiono (Indonesian Journal Publisher, 2024)
Cost and time optimization is an important aspect of project management that aims to achieve optimal efficiency in the use of resources. Time Cost Trade Off (TCTO) method is often used to manage the relationship between time and cost in project completion. This research analyzes cost and time op-timization on construction projects using Primavera P6 software. In optimi-zation with the addition of working hours, 4 alternatives were carried out, namely the addition of 1 hour, 2 hours, 3 hours, and 4 hours of work, the re-sults obtained were a shorter duration but the total cost was getting bigger. Whereas in the alternative of adding workers as many as 1 worker and 2 workers, the optimization results obtained a shorter duration and a reduced total cost. Thus, the TCTO method and the use of Primavera P6 proved ef-fective in identifying the most efficient optimization strategy to achieve pro-ject success on time and within budget.